Combined feedback–feedforward control of Ćuk CCM converter for achieving fast transient response - Byeongcheol Han; Seok‐Min Wi; Minsung Kim (IET Circuits, Devices and Systems)
Abstract The Ćuk converters operating in continuous conduction mode (CCM) can be preferred in applications such as microprocessor power delivery and pulsed load because these circuits have advantages of being able to step up/down, a small number of power components, and low input/output current ripples. However, they show poor transient performance due to right‐half‐plane‐zeros (RHPZs) in the closed‐loop transfer function of the Ćuk CCM converter. To enhance the transient response, a combined feedback–feedforward control for the Ćuk CCM converter is proposed. The proposed control scheme comprises a feedback control signal based on a Lyapunov function and a duty‐ratio feedforward control signal. A Lyapunov‐function‐based controller (LBC) achieves fast dynamic response even under large‐signal variations from the operating point. The duty ratio feedforward controller (DFFC) is developed to predict the effect of the disturbances and compensate it, while alleviating the burden of LBC. The proposed control logic makes the closed‐loop system of the Ćuk CCM converter globally exponentially stable and thus provides a fast transient response even under large‐signal variations. To construct the proposed controller, the authors make use of the large‐signal averaged model of the Ćuk CCM converter, and consider the parasitic elements. To verify the proposed control scheme, numerical simulations and experimental tests are conducted.